SFMOMA Painting and Sculpture Highlights - Bishop, Janet; Bryan-Wilson, Julia; Grynsztejn, Madeleine; Haas, Elise S.; Hutton, Molly; Kim, Clara; McDowell, Tara; Weber, John S.; SFMOMA (San Francisco Museum of Modern Art) San Francisco (San Francisco : San Francisco Museum of Modern Art, 2002)
The San Francisco Museum of Modern Art is recognized internationally as a premier destination for the viewing of twentieth- and twenty-first century art. This volume serves as an introduction to the outstanding holdings of the painting and sculpture collection, which includes landmark works by artists such as Henri Matisse, Frida Kahlo, René Magritte, Andy Warhol, and Richard Diebenkorn. An introductory essay by Madeleine Grynsztejn, Elise S. Haas Senior Curator of Painting and Sculpture at SFMOMA, outlines the general scope and evolution of the painting and sculpture collection, in particular its remarkable growth since the Museum's 1995 move to a new building designed by Mario Botta. Additional essays provide focused discussions on individual artworks and their broader significance within the history of art.
Arneson, Robert ; Bechtle, Robert ; Beckmann, Max ; Bourgeois, Louise ; Brancusi, Constantin ; Braque, Georges ; Brown, Joan ; Calder, Alexander ; Colescott, Robert ; Cornell, Joseph ; Davis, Stuart ; Derain, André ; Diebenkorn, Richard ; Dove, Arthur ; Duchamp, Marcel ; Fritsch, Katharina ; Gober, Robert ; Gonzalez-Torres, Felix ; Guston, Philip ; Hesse, Eva ; Hodges, Jim ; Jawlensky, Alexej von ; Jess ; Johns, Jasper ; Johnson, Sargent ; Kahlo, Frida ; Kelly, Ellsworth ; Kiefer, Anselm ; Klee, Paul ; Kline, Franz ; de Kooning, Willem ; Koons, Jeff ; LeWitt, Sol ; Lichtenstein, Roy ; Magritte, René ; Marc, Franz ; Marioni, Tom ; Marshall, Kerry James ; Martin, Agnes ; Matisse, Henri ; Matta-Clark, Gordon ; Miro, Joan ; Mitchell, Joan ; Mondriaan, Piet ; Motherwell, Robert ; Nauman, Bruce ; Nevelson, Louise ; Newman, Barnett ; O'Keeffe, Georgia ; Park, David ; Picasso, Pablo ; Polke, Sigmar ; Pollock, Jackson ; Rauschenberg, Robert ; Richter, Gerhard ; Rivera, Diego ; Rothko, Mark ; Ruscha, Ed ; Ryman, Robert ; Salcedo, Doris ; Serra, Richard ; Sheeler, Charles ; Smithson, Robert ; Stella, Frank ; Stella, Joseph ; Still, Clyfford ; Sze, Sarah ; Tamayo, Rufino ; Tanguy, Yves ; Thiebaud, Wayne ; Tuttle, Richard ; Walker, Kara ; Warhol, Andy
Engels
boek